2007
DOI: 10.3168/jds.2007-0006
|View full text |Cite
|
Sign up to set email alerts
|

Objective Determination of Claw Pain and Its Relationship to Limb Locomotion Score in Dairy Cattle

Abstract: We hypothesized that claw and foot pain could be objectively determined and have a strong effect on limb locomotion. Claw pain was measured using hoof testers equipped with a pressure gauge. Soft tissue pain was evaluated with an algometer. Pain was determined as the maximum pressure recorded at the time the limb was withdrawn following claw or soft tissue compression with the hoof tester or algometer. Locomotion scores and claw and soft tissue pain were determined on 263 Holstein cows from 2 commercial dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 18 publications
4
81
0
1
Order By: Relevance
“…For example, Dyer et al (2007) used hoof pressure testers as a way to measure pain. They found that cows that were sensitive to this pain assessment also had higher locomotion scores.…”
Section: Gait Assessment In Dairy Cattlementioning
confidence: 99%
“…For example, Dyer et al (2007) used hoof pressure testers as a way to measure pain. They found that cows that were sensitive to this pain assessment also had higher locomotion scores.…”
Section: Gait Assessment In Dairy Cattlementioning
confidence: 99%
“…There have been several studies using mechanical nociception tests to quantify painful and non-painful states using This is a manuscript of an article is from Journal of Animal Science 92 (2014): 3073, doi:10.2527/jas.2013-7521. lameness as a model in sheep (Ley et al, 1989), dairy cattle (Dyer et al, 2007) and most recently in lame sows (Nalon et al, 2013; Tapper et al, 2013). These studies concluded that the mechanical nociceptive tests were able to quantify decreased mechanical thresholds when animals were in painful lameness states.…”
Section: Mechanical Nociceptive Threshold (Mnt) Testmentioning
confidence: 99%
“…The United States Department of Agriculture (USDA;2007) reported that lameness was the third most common reason producers cull gilts and sows from the breeding herd (15.2%), compared to age (36.6%) and reproductive failure (26.3%). It is unclear which types of lameness result in acute or chronic pain, but it is recognized that the duration and intensity of pain is an individual experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, cows suffering from clinical foot disorders have a higher probability of being culled (Machado et al 2010). Even though the majority of foot disorders occur subclinically without causing lameness (Dyer et al 2007), this ''does not imply that an animal is not suffering'' (Somers 2004).…”
Section: Introductionmentioning
confidence: 99%